Applicability of Colors in Interior Spaces of Buildings - Mohammed Abdulqader Ali Alqamadi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study investigates the applicability of color in interior spaces, synthesizing psychological, cultural, and functional dimensions to establish evidence-based design guidelines. Through a qualitative-dominant mixed-methods approach, we analyze secondary data from peer-reviewed research, case studies (e.g., Alma de Luce projects), and industry standards (WELL Building Standard v2). Thematic coding reveals that color significantly impacts occupant well-being (e.g., blue reduces stress, red enhances energy) and spatial perception (e.g., light tones expand rooms). Cross-cultural comparisons highlight divergent symbolism—white signifies purity in Western contexts but mourning in East Asia—underscoring the need for localized strategies. Quantitative benchmarks, including Light Reflectance Value (LRV) thresholds and melanopic lighting metrics, validate these findings, demonstrating that optimal contrast ratios (30–70%) improve wayfinding by 27% (Wang & Durmus, 2025). The study culminates in a decision matrix integrating psychological effects, cultural relevance, and performance criteria (e.g., circadian alignment) for designers. Key limitations include reliance on secondary data and Western-centric biases in industry standards. Results advocate for human-centric design that balances aesthetics with scientific rigor, particularly in healthcare and workplace environments. Future research should prioritize post-occupancy validations and Global South case studies to address geographic gaps. This work bridges historical color theories (Chevreul, 1855; Itten, 1961) with contemporary practices, offering a holistic framework for intentional color application in architecture and interior design.